The Concept of Islamic Education Regarding Human Body Care As Prevention Genocide - Muntohar; Titik Kusumawinakhyu; Abdul Latif (Al-Qalam Institue, 2025)
This study aims to explore the role of Islamic education in preventing genocide, emphasising values such as respect for life, justice, compassion, and human brotherhood (ukhuwah basyariah). This research is motivated by the increasing violence based on ethnic, religious, and cultural differences that have led to conflict and genocide. The method used is qualitative research with a descriptive approach, examining Islamic religious texts such as the Quran and Hadith, as well as related literature, to analyse the principles of Islamic education for fostering tolerance and reducing violence. The results show that the principles of hifzh al-nafs (the protection of life), the prohibition of injustice, and the teaching of compassion in Islamic education play a crucial role in building a society that respects human rights and prevents genocidal behaviour. In conclusion, Islamic education can be an effective tool for preventing genocide by instilling the values of justice, compassion, and brotherhood. This research contributes to an understanding of the application of Islamic education in preventing violence and building global peace.